Evaluation of perfusion index as a screening tool for prediction of hypotension and shivering in cesarean section - Parita Gandhi; Divya Kheskani; Heena Sunil Chhanwal; Rekha Nilesh Solanki; Meet Shah; Aayushi Singh (Wolters Kluwer Medknow Publications, 2023)
Aim: The aim of this study was to determine whether a baseline perfusion index (PI) can predict hypotension and shivering after spinal anesthesia for cesarean section. Materials and Methods: In this prospective, observational study, 100 parturients were divided into two groups on the basis of baseline PI. Group I included parturients with PI of <3.5, and Group II included parturients with PI values ≥3.5. Spinal anesthesia was performed with hyperbaric 2 ml of 0.75% ropivacaine at L3-L4 or L2-L3 interspace. Hypotension was defined as mean arterial pressure <65 mmHg. PI and blood pressure were monitored at baseline, every 2 min for 12 min, and every 10 min until 120 min. Shivering was observed until 120 min according to the Crossley and Mahajan scale. Statistical analysis was performed using Chi-square test, independent sample t-test, and Mann-Whitney U-test. Results: Baseline PI significantly correlated with the number of episodes of hypotension. The overall incidence of hypotension was significantly higher in parturients with baseline PI ≥3.5 (79.16%) compared to those with PI <3.5 (33.33%), and parturients with preoperative PI <3.5 had a greater risk of post-anesthetic shivering. Conclusions: Perfusion Index serves as an excellent tool for predicting hypotension and shivering in pregnant patients.